2016
DOI: 10.1080/13510002.2016.1239867
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of wild Corni fructus methanolic extract against acute alcoholic liver injury in mice

Abstract: (2017) Protective effect of wild Cornifructus methanolic extract against acute alcoholic liver injury in mice, Redox Report, 22:6,[338][339][340][341][342][343][344][345]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The current research results show the hepatoprotective effect on polysaccharides against alcohol-induced liver injury by attenuating the expression of CYP2E1 and by enhancing the protective role of anti-oxidative defense system. Similar studies have previously shown that a wide range of natural products and their active substances have strong CYP2E1 inhibitory capacity [ 41 , 42 ]. In this experiment, En-OPS can increase the activities of ADH and ALDH and reduce CYP2E1 levels, indicating that En-OPS has a positive effect on alcohol metabolism.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The current research results show the hepatoprotective effect on polysaccharides against alcohol-induced liver injury by attenuating the expression of CYP2E1 and by enhancing the protective role of anti-oxidative defense system. Similar studies have previously shown that a wide range of natural products and their active substances have strong CYP2E1 inhibitory capacity [ 41 , 42 ]. In this experiment, En-OPS can increase the activities of ADH and ALDH and reduce CYP2E1 levels, indicating that En-OPS has a positive effect on alcohol metabolism.…”
Section: Discussionsupporting
confidence: 72%
“…Gavage was processed with a syringe once daily and the entire experiment procedure lasted for 20 consecutive days. On the 21st day, all mice, except those in the NC group, were orally administered with 8 mL/kg of 50% alcohol solution every 6 h for four times to induce hepatic injury by the previous reports [ 42 , 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…GSH content was quantified according to the method of Moron, Depierre, and Mannervik () based on its reaction with 5,5′‐dithiobis‐(2‐nitrobenzoic‐acid). AHR activity was evaluated based on the Fenton reaction (Jiang et al, ). Soluble protein concentration of homogenates was determined by the method of Bradford () using bovine serum albumin as standard.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 56 experimental mice were randomly assigned into 8 groups of 7 mice in each group (n=7). The reported protocol (Jiang et al, 2016) was exploited to modeling alcohol induced liver injury. Group 1 was the normal control group (NC group).…”
Section: Animal Experimentsmentioning
confidence: 99%
“…The microsomal preparation was conducted according to the method described by Jiang et al (2016), and the Bradford protein assay was used to estimate the protein content using bovine serum albumin as the standard (Tiangen Biotech, Beijing, China). Proteins were resolved by SDS-PAGE and transferred to PVDF membranes (Millipore Corporation, Boston, ME, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%